Antioxidant Potential of Essential Oils from Selected Medicinal Plants - Acila Baraa; Chelalga Roumaissa; Gadi Amani; Touahria Oula (Université of Eloued, 2025)
The plant kingdom is a rich reservoir of bioactive compounds known for their antioxidant properties. This study aims to evaluate the antioxidant activity of the essential oil of Cotula Cinerea and that of Origanum Majorana L, using standardized laboratory techniques. The essential oils were extracted from the plants using the hydrodistillation technique. The chemical composition of the oils was then analysed using Gas chromatography coupled with Mass Spectrometry (GC-MS). Upon identifying their constituents, Cotula Cinerea was found to contain 31 compounds, whereas Origanum Majorana L contained 42 compounds. The antioxidant activity was also evaluated using two methods: the DPPH free radical scavenging assay, Superoxide radical scavenging assay O2 . - . The results showed that both essential oils possess antioxidant activity, with a noticeable variation in efficacy between them. Cotula Cinerea exhibited higher antioxidant activity compared to Origanum Majorana L in both assays. Molecular docking studies were performed to predict the interaction of key compounds in essential oils with antioxidant enzymes, and the results showed strong interactions that support the potential mechanisms of their antioxidant activity at the molecular level. The study demonstrated that the essential oils of Cotula Cinerea and Origanum Majorana L contain natural compounds with antioxidant activity, supporting their potential use as natural supplements in the food or pharmaceutical industries. These findings also encourage further studies to evaluate their effectiveness in biological models
Keywords: Essential Oil; antioxidant activity; Cotula Cinerea; Origanum Majorana L; زيت أساسي ، نشاط مضاد للأكسدة، شيحية الإبل، المردقوش